Feedback Equivalence of 1-dimensional Control Systems of the 1-st Order - Lychagin, V.V. (Інститут математики НАН України, 2009)
The problem of local feedback equivalence for 1-dimensional control systems of the 1-st order is considered. The algebra of differential invariants and criteria for the feedback equivalence for regular control systems are found.